A multicentre, randomised, sham-controlled trial on REmote iSchemic conditioning In patients with acute STroke (RESIST) – Rationale and study design. (March 2020) - Blauenfeldt, Rolf A; Hjort, Niels; Gude, Martin F; Behrndtz, Anne B; Fisher, Marc; Valentin, Jan B; Kirkegaard, Hans; Johnsen, Søren P; Hess, David C; Andersen, Grethe
Rationale: Remote ischaemic conditioning, applied in the prehospital setting and continued in-hospital, may improve functional outcome in patients with acute ischaemic stroke and intracerebral haemorrhage. Aims: To evaluate whether combined remote ischaemic per- and postconditioning can improve long-term functional outcome in acute ischaemic stroke and intracerebral haemorrhage patients. Methods and design: Danish multicentre, prospective, randomised, patient-assessor blinded, sham-controlled study. Adult patients with a putative stroke identified prehospital with symptom duration <4 h, who are independent in daily activities will be randomised 1:1 to remote ischaemic conditioning or Sham-remote ischaemic conditioning. The treatment protocol will be five cycles, each consisting of 5 min with a blood pressure cuff inflation and 5 min with a deflated cuff placed on the upper extremity. The cuff pressure for remote ischaemic conditioning will be 200 mmHg–285 mmHg according to the individual systolic blood pressure and 20 mmHg sham-remote ischaemic conditioning during inflation. The study is approved as an acute study and consent is waived in the acute phase. Sample size estimation: For a 7% increased odds for a beneficial shift on the modified Rankin Scale at a significance level of 5% and power of 90%, 1000 patients with a target diagnosis of acute ischaemic stroke and intracerebral haemorrhage and a total of 1500 patients with a prehospital presumed stroke will be included. Study outcomes: The primary outcome will be the modified Rankin Scale score measured at three-month follow-up (analysed using ordinal logistic regression). ClinicalTrials.gov Identifier: NCT03481777.